Perth punk and the construction of urbanity in a suburban city1. Issue 1 (30th November 2015) - Trainer, Adam
Abstract: As a musical form, punk is often associated with urbanity, as embodied in the scenes in both London and New York, and in an Australian national context by the scenes in Melbourne and Sydney. In Perth, Western Australia – a primarily middle-class suburban city without a distinct inner city – punk was expressed differently. While the music itself exemplified many of the stylistic traits associated with the genre, punk in Perth was articulated through the city's isolation, its affluence and its suburban nature. Utilising interviews with key players in the Perth punk scene of the late 1970s, this paper seeks to illustrate the ways in which urbanity was constructed and voiced through Perth punk, in a city that constructed itself in opposition to traditional notions of the inner city's urban lived environment.